Non‐invasive electromyographic estimation of motor unit number in the external anal sphincter of the rat. Issue 1 (8th September 2017) - Zhang, Chuan; Munoz, Alvaro; Lai, H. Henry; Boone, Timothy; Zhang, Yingchun
Abstract : Aims: The external anal sphincter (EAS) is essential for maintaining fecal continence. Neurological disorders or traumatic injuries to muscle and nervous systems could lead to EAS denervation. Currently, there are no techniques available to document global innervation changes in the EAS in vivo. The aim of this study was to develop a novel approach to non‐invasively estimate the number of functioning motor units (MUs) in the EAS and validate with immunofluorescent techniques in rats. Methods: Intra‐rectal surface electromyography (EMG) signals of the EAS, induced by a series of intra‐vaginally delivered pudendal nerve stimulations with different intensities, were recorded. Variation in EMG responses at different intensities was used to estimate the value of a single motor unit potential (SMUP) in order to perform the proposed EAS motor unit number estimation (MUNE) approach. The EAS MUNE was tested in 12 female Sprague‐Dawley rats, and validated by comparing against the EAS myofiber counting results achieved by performing immunostaining of acetylcholine receptors in 7 of the 12 rats. Results: The mean MU number was 35 ± 9, with an averaged SMUP size of 52.49 ± 20.39 μV. The mean number of successfully identified myofibers was 652.7 ± 130.6 myofiber/EAS. Significance of linear regression between the immunofluorescent results and the MUNE was confirmed ( P < 0.01). Conclusions: Our study represents the first effort to non‐invasively assess the innervation of the EAS in vivo using the rat as a pre‐clinical model. This approach can potentially enable future clinical applications for advanced diagnosis and treatment of neurogenic EAS disorders.